Familial Mediterranean fever and asthma. (16th February 2021) - Tsur, Avishai M; Watad, Abdulla; Gendelman, Omer; Nissan, Daniel; Cohen, Arnon D; Amital, Howard
Abstract: Objective: To assess the association between FMF and asthma. Methods: This study was designed as a cross-sectional study. All patients diagnosed with FMF between 1 January 2000 and 31 December 2016 who were prescribed colchicine were included in the study. Controls were matched by sex, date of birth, residential socioeconomic status and country of birth. Logistic regression models were used to determine the odds ratio for asthma in FMF patients and controls. Results: A total of 7098 FMF patients who were prescribed colchicine were identified. Of them, 3547 (50%) were females, 3632 (51%) were of low residential socioeconomic status and 6160 (87%) were born in Israel. Their median age at the end of follow-up was 37 years (23–54). In an unadjusted logistic regression, FMF was associated with asthma [odds ratio (OR)=1.33, 95% CI: 1.17, 1.51; P  <0.001]. The association persisted after adjusting for sex, socioeconomic status and country of birth (OR=1.33, 95% CI: 1.18, 1.52; P  <0.001) Conclusion: FMF is positively associated with asthma. Further research is required to validate our results and explore possible explanations of this association. These findings cast doubt on previous studies implying FMF to be a protective factor from asthma.